2023
DOI: 10.1680/jensu.22.00014
|View full text |Cite
|
Sign up to set email alerts
|

Building information modelling a key for construction industry recovery post-Covid-19

Abstract: Several countries have introduced, and several kinds of research have discussed the performance of Building Information Modelling (BIM) as an information technology trend. Despite its potential impact on construction performance, this concept has not attracted the attention of many countries like Morocco. COVID-19 broke out when the architecture, engineering, and construction (AEC) industry was suffering from several shortcomings, mainly the poor technology exploitation cited in the literature. Although this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…The result of this paper regarding the use of BIM to enhance the resilience of AECO sector against Covid-19 disruption is consistent with the result of Wang et al (2023). BIM has the potential to strengthen the resilience of the AECO sector, as Idrissi et al (2022) indicated in their study that BIM has a swift uptake globally.…”
Section: Insert Table ⅳ Heresupporting
confidence: 84%
“…The result of this paper regarding the use of BIM to enhance the resilience of AECO sector against Covid-19 disruption is consistent with the result of Wang et al (2023). BIM has the potential to strengthen the resilience of the AECO sector, as Idrissi et al (2022) indicated in their study that BIM has a swift uptake globally.…”
Section: Insert Table ⅳ Heresupporting
confidence: 84%
“…Such a megaproject as the Mohamed VI Tower is armed with several approaches to meet the desired quality. BIM was deployed during the design phase as a technological approach to collaborative work (Idrissi Gartoumi et al , 2022b)and performance improvement in design, dimensioning, error detection and waste minimisation (Idrissi Gartoumi et al , 2022c). In addition to BIM, the tower project follows the LEED Gold (Leadership in Energy and Environmental Design) and High-Quality Environmental certification.…”
Section: Project Overviewmentioning
confidence: 99%
“…BIM drives the direction of training and adoption, especially from an organisational perspective. A specific research direction investigates effective BIM training strategies for small firms that frequently encounter resource constraints in the construction industry [9,10]. This finding is important, as larger companies generally have more resources to train their employees.…”
Section: Introductionmentioning
confidence: 99%